What Are the Effects of Capsular Plication on Translational Laxity of the Glenohumeral Joint: A Study in Cadaveric Shoulders. Issue 7 (July 2018) - Mayer, Stephanie W.; Kraszewski, Andrew P.; Skelton, Anne; Kontaxis, Andreas; Warren, Russell
Abstract: Background: Surgical treatment for shoulder instability generally involves labral repair with a capsular plication or imbrication. Good results are reported in both open and arthroscopic procedures, but there is no consensus on the amount or location of capsular plication that is needed to achieve stability and anatomic anterior, posterior, and inferior translation of the joint. Questions/purposes: (1) What are the separate and combined effects of increasing plication magnitude and sequential additive plications in the anterior, posterior, and inferior locations of the joint capsule on glenohumeral joint translation in the anterior, posterior, and inferior directions? (2) What plication location and magnitude restores anterior, posterior, and inferior translation to a baseline level? Methods: Fourteen cadaveric shoulders were dissected down to the glenohumeral capsule and underwent instrumented biomechanical testing. Each shoulder was loaded with 22 N in anterior, posterior, and inferior directions at 60° abduction and neutral rotation and flexion and the resulting translation were recorded. Testing was done over baseline (native), stretched (mechanically stretched capsule to imitate a lax capsule), and 5-mm, 10-mm, and 15-mm plication conditions. Individually, for each of the 5-, 10-, and 15-mm increments, plications were done in a fixed sequential order starting with anterior plication at the 3 o'clock position (Sequence I), then adding posterior plication at the 9 o'clock position (Sequence II), and then adding inferior plication at the 6 o'clock position (Sequence III). Each individual sequence was tested by placing 44 N (10 pounds) of manual force on the humerus directed in an anterior, posterior, and inferior direction to simulate clinical load and shift testing. The effect of plication magnitude and sequence on translation was tested with generalized estimating equation models. Translational differences between conditions were tested with paired t-tests. Results: Translational laxity was highest with creation of the lax condition, as expected. Increasing plication magnitude had a significant effect on all three directions of translation. Plication location sequence had a significant effect on anterior and posterior translation. An interaction effect between plication magnitude and sequence was significant in anterior and posterior translation. Laxity in all directions was most restricted with 15-mm plication in anterior, posterior, and inferior locations. For anterior translational laxity, at 10-mm and 15-mm plication, there was a progressive decrease in translation magnitude (10-mm plication anterior only: 0.46 mm, plus posterior: 0.29 mm, plus inferior, -0.12 mm; and for 15-mm anterior only: -0.53 mm, plus posterior: -1.00 mm, plus inferior: -1.66 mm). For posterior translational laxity, 10-mm and 15-mm plication also showed progressive decrease in magnitude (10-mm plication anterior only: 0.46 mm, plus posterior: -0.25 mm, plus inferior: -1.94; and for 15-mm anterior only: 0.14 mm, plus posterior: -1.54 mm, plus inferior: -3.66). For inferior translational laxity, tightening was observed only with magnitude of plication (anterior only at 5 mm: 0.31 mm, at 10 mm: -1.39, at 15 mm: -3.61) but not with additional plication points (adding posterior and inferior sequences). To restore laxity closest to baseline, 10-mm AP/inferior plication best restored anterior translation, 15-mm anterior plication best restored posterior translation, and 5 mm posterior with or without inferior plication best restored inferior translation. Conclusions: Our results suggest that (1) a 10-mm plication in the anterior and posterior or anterior, posterior, and inferior positions may restore anterior translation closest to baseline; (2) 10-mm anterior and posterior or 15-mm anterior plications may restore posterior translation closest to baseline; and (3) 5-mm anterior and posterior or anterior, posterior, and inferior plications may restore inferior translation closest to baseline. Future studies using arthroscopic techniques for plication or open techniques via a true surgical approach might further characterize the effect of plication on glenohumeral translation. Clinical Relevance: This study found that specific combinations of plication magnitude and location can be used to restore glenohumeral translation from a lax capsular state to a native state. This information can be used to guide surgical technique based on an individual patient's degree and direction of capsular laxity. In vivo testing of glenohumeral translation before and after capsular plication will be needed to validate these cadaveric results.